Strategy for Growing the Business of Representative Office Company in Iron and Steel Industry - Herry Winarso; Anh Dung Do (IPTEK Journal of Proceedings Series, 2020)
Iron and steel industry is among the essential strategic groups of the national industry since iron and steel products are not only raw materials for metal-based manufacture industries but also as pillars of development in infrastructure. The development of the iron and steel industry requires comprehensive handling; in the mastering of processing technology and the resources added value. The iron and steel industry is the “Backbone” in supporting the development of the national economy. Therefore, the Government’s role becomes crucial in developing the national iron and steel industry. Initially, the Indonesian steel industry was the largest in ASEAN, however over time, the position of Indonesian declines and no longer the largest. DAN is one of the three top manufacturers of plants and machines for the steel-making industry in the world. The unavailability of adequate government protection to domestic producers made imported steel products streamed heavily in all upstream and downstream sectors. This situation made the steel producer cannot grow and become stagnant in income; it cannot compete in costs; therefore, cannot invest and innovate effectively. The unavailability of the significant investment made DAN business in Indonesia become tough to grow. The purpose of the research is to develop a business strategy for DAN representative office to grow its business in Indonesia and choose a value proposition to the Indonesian market. To achieve the research objective, data collection in the method of interviews into Indonesia iron and steel industry stakeholders, along with a direct survey questionnaire into the experts to understanding industry situation and stakeholders' perspective of DAN overall performance. The various analysis framework, named PESTEL, Five Forces Porter, SWOT, were utilized to understand Indonesia iron and steel market, and company internal advantages and disadvantages in responding to it. The result of strategies is implemented with sequences: costing evaluation, financing support, human resources, partnership development, and investment.